The School as a Protective Factor against Suicidal Behaviour in Childhood and Adolescence - Delgado Moral, Carmen (Avances en Supervisión Educativa, 2025)
The article highlights the relevance of schools as a key pillar in the prevention of adolescent suicide. In the face of risky behaviors, it highlights the demand for the implementation of protocols that respond to them, as well as the relevance of teacher training to identify and act on the prevention of suicide, under the provisions of the Organic Law. 8/2021, of June 4, on comprehensive protection of children and adolescents. The text analyzes different risk factors for suicidal behavior, such as bullying, as well as support factors in adolescence. It highlights the importance of evaluating the effectiveness of the implementation of the protocols, as well as the difficulties associated with their activation. Finally, the article analyzes differentiating aspects in the activation of protocols for the prevention of suicidal behavior in adult students, as well as the role of educational inspection as a guarantor of the protection of rights.